Socio-economic Empowerment of Women Through Micro-entrepreneurship: Evidence from Odisha, India. (October 2019) - Senapati, Asis Kumar; Ojha, Kalpana
Micro, small and medium enterprises play a pivotal role in the country which can contribute to women empowerment providing them employment opportunity. It is a key force in improving the economic condition of women providing employment to highly qualified as well as less qualified women for their overall development and helps to recognize their inherent ability to be engaged in the non-agricultural sector when employment in the agricultural sector is static. The present study attempts to assess the socio-economic empowerment of women through entrepreneurship and identify several problems faced by them in managing the enterprise. A total of 100 samples were surveyed for the purpose of the study. Simple random sampling has been used to collect data from 30 registered entrepreneurs. Through snowball sampling, 70 unregistered entrepreneurs were interviewed in the area. Both quantitative and qualitative data have been collected through a structured questionnaire using direct interview method. OLS regression and ordered logistic regression models have been used to explore the determinants of empowerment. Again, different constraints the entrepreneurs confronted during initiation and current management have been explored. The key economic variables are income, expenditure and enterprise decision making that are likely to increase the economic empowerment scores. All social empowerment variables except physical mobility are likely to increase social empowerment scores. The prime constituents of obtaining high overall empowerment status are income, self-employment, participation in domestic decision-making, independently managing personal matters, credit management, leisure, unpaid work, confidence in one's own self, and social recognition. The study found that finance is the key challenge in start-ups and running expenses of enterprises. In addition, work-life and family imbalance, and marketing are recognized as prominent, followed by lack of lucrative price and heavy workloads.